2005
DOI: 10.1136/bjsm.2005.018358
|View full text |Cite
|
Sign up to set email alerts
|

Research approaches to describe the mechanisms of injuries in sport: limitations and possibilities

Abstract: A number of different methodological approaches have been used to describe the inciting event for sports injuries. These include interviews of injured athletes, analysis of video recordings of actual injuries, clinical studies (clinical findings of joint damage are studied to understand the injury mechanism, mainly through plain radiography, magnetic resonance imaging, arthroscopy, and computed tomography scans), in vivo studies (ligament strain or forces are measured to understand ligament loading patterns), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
139
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(155 citation statements)
references
References 113 publications
1
139
0
9
Order By: Relevance
“…However, even if these few details are known, we still lack vital knowledge about the injury mechanisms. A complete biomechanical description should quantify whole-body and knee kinematics, loading directions, magnitudes, and rates (Krosshaug, Andersen, Olsen, Myklebust, & Bahr, 2005).…”
Section: Mechanismsmentioning
confidence: 99%
“…However, even if these few details are known, we still lack vital knowledge about the injury mechanisms. A complete biomechanical description should quantify whole-body and knee kinematics, loading directions, magnitudes, and rates (Krosshaug, Andersen, Olsen, Myklebust, & Bahr, 2005).…”
Section: Mechanismsmentioning
confidence: 99%
“…Although interpretation of the results is worthy, it is difficult to predict to what extent the observed proprioception capacities of the subjects in a laboratory setting exposes the athlete to increased risk of injury on the field. 67 For example, for TTDPM and FS, the subjects were tested in a supine and side lying position. This is not the position at which hip injuries occur during practice or a game.…”
Section: Applicabilitymentioning
confidence: 99%
“…As a result, the interpretation of differences in noncontact ACL injury rates, especially over time, is problematic. This limitation has also been discussed in a broader context by Krosshaug et al 7 Another example occurs when one attempts to compare results from different studies. In the area of ACL intervention studies, Gilchrist et al 12(p1478) conducted a randomized trial of an intervention program in 61 NCAA female soccer teams and found a positive effect.…”
Section: Negative Consequences Of the Absence Of A Clear Definition Omentioning
confidence: 99%
“…Patient narratives are an imperfect source of injury-event data because they depend on accurate recall of events that occur rapidly. 7 We believe that the information obtained in the JUMP-ACL study is sufficiently accurate to permit development of the classification system outlined above. However, replication and refinement by other researchers is needed.…”
Section: A Classification System For Contactmentioning
confidence: 99%
See 1 more Smart Citation